ANALISIS KRITIS DISTORSI KONSTRUKSI WACANA RADIKALISME DALAM PEMBERITAAN MEDIA MASSA DAN MEDIA SOSIAL DI INDONESIA - Riza Anggara Putra; Iswahyudi Iswahyudi (Proceeding of Conference on Strengthening Islamic Studies in The Digital Era, 2021)
This article explores the distortion or bias in mass media reporting through the construction of terrorism discourse in mass media reporting. This is based on the interdependence relationship between the mass media and the terrorists themselves. Through discourse analysis, it shows how the shift in the construction of mass media discourse is influenced by external factors in the form of a national political context that is influenced by global issues. In addition, the bias from reporting on acts of terrorism is in the form of labeling Islam so that it has an impact on the creation of Islamophobia. The most prominent research finding through the construction of terrorism discourse is that there is a strong relationship between terrorist actors and the mass media. For the mass media, acts of terrorism are considered a magnitude in carrying out the economic function of the mass media. For terrorists, the continuous mass media coverage of terrorist acts is a medium to maintain their existence in society. Keywords: Distortion, Terrorism Discourse, Mass